PENDAMPINGAN MASYARAKAT DALAM REVITALISASI DESA WISATA KOKOKAN DI BANJAR PETULU GUNUNG - Pande Putu Dwi Novigga; Ni Putu Ratih Pradnyaswari; Putu Ayu Sita Laksmi (Universitas Dwijendra, 2024)
Petulu Village is a suburb of Ubud which is used as an area for expanding Ubud tourism. Petulu Village is famous for one of the uniquenesses in one of the hamlets, namely Banjar Petulu Gunung. The uniqueness of this hamlet is that it has a gathering of thousands of Kokokan birds that live around the Banjar Petulu Gunung area. So that this uniqueness is used as a tourist attraction called the Kokokan tourist attraction. This Kokokan tourist attraction already has several accommodation facilities such as ticketing, toilets and a bale banjar as a meeting place. However, these facilities are considered less than optimal so that tourists are reluctant to pay. Kokokan birds are also located along the main road which is generally passed by the community and tourists so that without having to pay, tourists can see the birds. This tourist attraction has been managed by the local Pokdarwis. But until now the tourist attraction has not been managed properly so that it has not been profitable in terms of economy. These problems must be resolved together by the relevant Village Stakeholders, the Community and Academics in order to obtain optimal quality tourist attractions. Of course, some of the solutions offered are related to the field of science of the implementing team, namely providing ideas for a master plan for the development of the Kokokan tourist attraction and its tourism development management. The hope of this PKM is to help develop the potential of the Village to become an independent Tourism Village.